The Involvement of HLA Class II Alleles in Multiple Sclerosis: A Systematic Review with Meta-analysis. (6th November 2019) - De Silvestri, A.; Capittini, C.; Mallucci, G.; Bergamaschi, R.; Rebuffi, C.; Pasi, A.; Martinetti, M.; Tinelli, C.
Abstract : Multiple Sclerosis (MS) displays a heterogeneous clinical onset and progression, which are mostly unpredictable, but demyelination of the central nervous system (CNS) leads to substantial deficits of sensory, motor, autonomic, and neurocognitive functions. Considering all genetic studies on MS, including the advanced genome-wide association studies, the risk linked to HLA alleles remains the highest among other susceptibility genetic variants. However, given the genetic variability of HLA alleles in different ethnic groups, we conducted a systematic review of reviews and meta-analyses aiming at summarizing all the results on the association between MS and HLA class II genes. We systematically searched meta-analyses and systematic reviews dealing with MS and HLA in all ethnicities. From 154 records, we included 5 articles collecting HLA data from 15, 232 MS patients and 24, 194 ethnically matched controls. DRB1∗ 15 (OR ranging from 1.39 in Chinese Han to 2.59 in Caucasians) and DQB1∗ 06:02 (OR ranging from 1.91 in Caucasians to 2.49 in Colombian) alleles confer an increased risk for MS transethnically (Caucasians, Chinese, South Americans, Carribeans, Middle Easterners, Japanese, and North Africans). DRB1∗ 01, DRB1∗ 09, DRB1∗ 11, DRB1∗ 12, and DRB1∗ 16 alleles were protective, in agreement with the type of amino-acidic (aa) residues (ranging from position 9 to 90) included in pockets 1, 4, 6, 7, and 9, which are most involved in peptide presentation. Changes in aa residues affect the capability of HLA molecules in binding myelin peptides. DQB1∗ 06:02 risk allele seems to be the most interesting target as humanized mice expressing only DQB1∗ 06:02 develop MS-like disease mediated by autoimmune reactions against myelin oligodendrocytic basic protein that stabilizes the myelin. Our summary of results from a high number of patients and controls suggests that allelic variants from both DQB1 and DRB1 genes are equally involved in MS susceptibility/protection transethnically.